Isometric versus isotonic contractions: Sex differences in the fatigability and recovery of isometric strength and high‐velocity contractile parameters. Issue 9 (15th May 2021) - Ha, Phuong L.; Dalton, Benjamin E.; Alesi, Michaela G.; Smith, Tyler M.; VanDusseldorp, Trisha A.; Feito, Yuri; Hester, Garrett M.
Abstract: The purpose of this study was to investigate potential sex differences in the fatigue‐ and recovery‐induced responses of isometric strength and power, as well as select dynamic contractile parameters after isometric and isotonic plantar flexor (PF) contractions. Healthy males ( n = 12; age = 21.8 ± 2.2 years) and females ( n = 14; age = 21.4 ± 2.5 years) performed a 2‐min maximal voluntary isometric contraction and 120 concentric isotonic (30% peak isometric torque) contractions of the PFs on separate visits. Isometric strength, isotonic power, as well as torque‐ and velocity‐related parameters were recorded before, immediately after, and throughout 10 min of recovery. Rate of EMG rise (RER) for the medial gastrocnemius (MG) and soleus was also obtained. All measures responded similarly between sexes after both fatiguing modalities ( p > 0.05), except RER of the MG which, in males demonstrated both, a greater decrease during isotonic contractions ( p = 0.038, η p 2 = 0.174) and more rapid recovery after isometric exercise ( p = 0.043, η p 2 = 0.166). Although not significant, a nearly large effect size was demonstrated for the fatigue‐induced decrease in isometric strength ( p = 0.061; d = 0.77) due to relative decreases tending to be greater in males (−29% vs. −17%). Regardless of fatiguing modality, sex differences were minimal for fatigue and recovery‐related responses in muscle function for the PFs, although the difference for RER may indicate a unique origin of fatigue. Further support for the disassociation between the response in isometric strength and power after fatiguing exercise was also demonstrated. Abstract : Fatigue‐induced decrements in isometric strength tend to be attenuated in females compared to males, but less is clear for isotonic power and the plantar flexors have seldomly been examined. We show that fatigability and recovery of strength and power were similar in male and females after isotonic and isometric exercise. This was despite the unique responses in rapid muscle activation between sexes.